Enhanced Raman Investigation of Cell Membrane and Intracellular Compounds by 3D Plasmonic Nanoelectrode Arrays. Issue 12 (23rd October 2018) - Caprettini, Valeria; Huang, Jian‐An; Moia, Fabio; Jacassi, Andrea; Gonano, Carlo Andrea; Maccaferri, Nicolò; Capozza, Rosario; Dipalo, Michele; De Angelis, Francesco
Abstract: 3D nanostructures are widely exploited in cell cultures for many purposes such as controlled drug delivery, transfection, intracellular sampling, and electrical recording. However, little is known about the interaction of the cells with these substrates, and even less about the effects of electroporation on the cellular membrane and the nuclear envelope. This work exploits 3D plasmonic nanoelectrodes to study, by surface‐enhanced Raman scattering (SERS), the cell membrane dynamics on the nanostructured substrate before, during, and after electroporation. In vitro cultured cells tightly adhere on 3D plasmonic nanoelectrodes precisely in the plasmonic hot spots, making this kind of investigation possible. After electroporation, the cell membrane dynamics are studied by recording the Raman time traces of biomolecules in contact or next to the 3D plasmonic nanoelectrode. During this process, the 3D plasmonic nanoelectrodes are intracellularly coupled, thus enabling the monitoring of different molecular species, including lipids, proteins, and nucleic acids. Scanning electron microscopy cross‐section analysis evidences the possibility of nuclear membrane poration compatible with the reported Raman spectra. These findings may open a new route toward controlled intracellular sampling and intranuclear delivery of genic materials. They also show the possibility of nuclear envelope disruption which may lead to negative side effects. Abstract : 3D plasmonic nanoelectrodes on multielectrode arrays allow for real‐time enhanced Raman monitoring of cell membrane permeabilization after in situ electroporation. The 3D nanostructures offer highly localized electroporation and high electromagnetic field enhancement for accurate Raman spectroscopy. The technique not only provides deep insights about the cell membrane resealing dynamics, but also reveals details on the intracellular environment.